Effect of Prey Density Dependent Predator Intraspecific Competition Rate in a Fear Induced Predator-Prey System - Mukherjee, Debasis (Discontinuity, Nonlinearity, and Complexity, 2026)
This article proposes and analyzes a fear-induced predator-prey model incorporating prey density-dependent predator intra-specific competition. The study focuses on how non-constant predator intra-specific competition affects the dynamics of the system. The investigation explores various aspects, including positivity, boundedness, local and global stability, uniform persistence, and Hopf bifurcation. Numerical simulation supports theoretical results, offering practical insights into the model behaviour.